Software for Developing Digital Media Competence in Future Teachers Based on Axiological Approach and the Status of Their Use - M. M. Mominova (International Journal of Formal Education, 2025)
The article analyzes the effectiveness of using electronic information and educational resources in the process of developing digital media competence of future teachers. Online learning opportunities are highlighted as one of the important aspects of improving media competence, since this approach creates favorable conditions for teachers to constantly work on themselves and develop professionally. It is also noted that the integration of digital technologies into the educational process also helps to understand ethical, social and cultural aspects.